2021
DOI: 10.3390/ijerph182111441
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training with Blood Flow Restriction Compared to Traditional Resistance Training on Strength and Muscle Mass in Non-Active Older Adults: A Systematic Review and Meta-Analysis

Abstract: Low-intensity training with blood flow restriction (LI-BFR) has been suggested as an alternative to high-intensity resistance training for the improvement of strength and muscle mass, becoming advisable for individuals who cannot assume such a load. The systematic review aimed to determine the effectiveness of the LI-BFR compared to dynamic high-intensity resistance training on strength and muscle mass in non-active older adults. A systematic review was conducted according to the Cochrane Handbook and reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
(93 reference statements)
1
20
0
Order By: Relevance
“…The results of our meta-analysis of 11 RCTs showed greater muscle strength gain with BFRt when compared to LIRT or normal activity, but no statistical difference between BFRt and HIRT was seen. Muscle strength gain after BFRt was also reported in recent meta-analyses [ 25 , 26 ], but these studies did not address the influence of training frequency. A research study reported that both BFRt and HIRT for 12 weeks can improve strength gain in older adults, and the benefits of BFRt and HIRT were not statistically different [ 38 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of our meta-analysis of 11 RCTs showed greater muscle strength gain with BFRt when compared to LIRT or normal activity, but no statistical difference between BFRt and HIRT was seen. Muscle strength gain after BFRt was also reported in recent meta-analyses [ 25 , 26 ], but these studies did not address the influence of training frequency. A research study reported that both BFRt and HIRT for 12 weeks can improve strength gain in older adults, and the benefits of BFRt and HIRT were not statistically different [ 38 ].…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the results of other meta-analyses showed that BFRt produced the same muscle strength gain as HIRT in older adults. [ 25 , 26 ]. These seemingly contradictory results in research studies and meta-analyses may be due to differences in the intervention protocol that was applied.…”
Section: Introductionmentioning
confidence: 99%
“…Although these results are promising, further investigation of BFRE in patients with HD and HF is needed in view of the beneficial effects on skeletal muscle, functional performance, and cardiorespiratory function in older subjects without heart disease. ( Hughes et al, 2017 ; Beckwée et al, 2019 ; Centner et al, 2019 ; Van Cant et al, 2020 ; Nitzsche et al, 2021 ; Rodrigo-Mallorca et al, 2021 ; Labata-Lezaun et al, 2022 ). Finally, there is a distinct need for additional randomized controlled trials examining the effects of BFRE in patients with HD and HF.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial literature of BFRE in older adults exists in which significant gains in strength and functional performance have been observed without report of adverse events. ( Beckwée et al, 2019 ; Centner et al, 2019 ; Rodrigo-Mallorca et al, 2021 ; Labata-Lezaun et al, 2022 ). Sophisticated tourniquets exist which allow for a more precise and personalized reduction in blood flow based on the limb occlusion pressure enabling safer and more precise BFRE in older adults and in patients with HD and HF.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of MBFR can result in increased skeletal muscle hypertrophy and strength for younger and older adults when combined with low-load resistance training (for systematic reviews and meta-analysis see [31][32][33][34][35][36]). The combination of resistance training with MBFR enhances skeletal muscle adaptations, however a lower load is required than those utilized with traditional resistance training programs.…”
Section: Introductionmentioning
confidence: 99%